Janice Holt Giles : A Writer's Life - Stuart, Dianne Watkins (Book collections on Project MUSE., 1998)
Dianne Watkins Stuart, for years the acknowledged expert on Giles's work, has traced the path of her unique life. Stuart walked around the small house where Giles's brother was born and The Kinta Years (1973) had its origin, wandered through the yard where The Plum Thicket (1954) grew, and made countless trips to Adair County, Kentucky, to trace the trails of the Piney Ridge trilogy (The Enduring Hills, Miss Willie, Tara's Healing) and seek out the day-to-day life of her later years.